Gereja Stasi Santa Sisilia di Kelurahan Semarapura Tengah, Klungkung: Sejarah, Akulturasi Budaya, dan Potensinya Sebagai Sumber Belajar Sejarah di SMA - Ni Komang Ari Mega Yanti; Tuty Maryati; Desak Made Oka Purnawati (Widya Winayata : Jurnal Pendidikan Sejarah, 2026)
This study aims to examine the history of the establishment of the Stasi Santa Sisilia Church in Semarapura Tengah Village, Klungkung Regency, analyze the form of Bali-Catholic cultural acculturation that developed within it, and identify its potential as a source for learning history at the high school level. The research uses a historical research method with a qualitative approach through the stages of heuristics, source criticism, interpretation, and historiography. The results of the study show that the Catholic community began to grow in Klungkung around 1980 through work assignments. Since they did not yet have a place of worship, the community began pioneering the church in 1985 by utilizing houses as mini churches. The construction of a permanent church began in 2011 and was inaugurated in 2014. Acculturation can be seen in the architecture that adopts Balinese ornaments such as carved kori doors, churches in Balinese style, and Kamasan Wayang-style reliefs with Gospel-themed stories, as well as a combination of baptismal names and Balinese naming systems. The presence of the church reflects religious tolerance. In the context of education, the history and social dynamics of Stasi Santa Sisilia Church are relevant as a learning resource in the Independent Curriculum, particularly in Phase F of Grade XI on the influence of European nations and the socio-cultural life of the community, as well as in Phase F of Grade XII on post-Reform socio-cultural life. This research contributes to strengthening the study of local history based on tolerance, acculturation, and multiculturalism. Keywords: History, Crurch, Cultural Acculturation, Learning Resources